Defining 'governmental authority' in the Malaysian competition act 2010: a quest for objectivity - Ahamat, Haniff; Abdul Rahman, Nasarudin (Inderscience Publishers, 2015)
This paper examines the concept of governmental authority, which serves as one of the grounds for excluding the application of the Malaysian Competition Act 2010. This concept is not defined in the 2010 Act. Thus, this paper explores the methods that help determine that an activity is governmental; hence, that it is subject to the Malaysian competition legislation. The methods identified so far are: 1) the existing definition of ‘governmental authority’ in competition legislation in selected jurisdictions including the EU; 2) the definition of governmental authority under the World Trade Organization (WTO)’s General Agreement on Trade in Services (GATS); 3) the definition of governmental acts in the context of state immunity under international law. This paper hypothesises that the term governmental authority lacks an established definition at the moment but it has clearly demarcated paradigms that may allow meaning to be given in an objective way despite the need to give attention to the unique political, economic and social environments in Malaysia